OPTIMASI PEMBERIAN PAKAN BUATAN PADA PENDEDERAN IKAN PATIN (Pangasionodon hypohpthalmus) DI KOLAM YANG DIPUPUK - Evi Tahapari; Didik Ariyanto; Bambang Gunadi (Jurnal Perikanan Universitas Gadjah Mada, 2008)
This research aimed to know the optimum formulated feeding patin (Pangasionodon hypohpthalmus) in the fingerling rearing in the fertilized pond. The fish seed were stocked in the fifteen cages of 3x2x1.25 m that were installed in the 50 m2 pond. Each cage was stocked with 600 fish with an average initial weight of 0.37 g and average body length of 2-3 cm. The treatments applied in this research were (A) without formulated feed, (B) 5% of biomass of formulated feed, (C) 10% of biomass of formulated feed, (D) 15% of biomass of formulated feed and (E) 20% of biomass of formulated feed. The protein level of the formulated feed was around 40%. The observations focused on the survival rates of fish, feed conversion ratios, body weight and length. The results showed that there were significant differences among fish treatments on the survival rates, feed conversion, weight and length growth (P<0,05). The survival rates of fish of the treatment A, B, C, D and E were 78.10%, 84.39%, 83.78%, 90.83% and 90.33%, respectively. The feed conversion of the feed given treatments i.e. B, C, D and E were 0.35, 0.62, 0.89 and 1.15, respectively. The weight growth during observation period (6 weeks) were 5.63 g, 15.29 g, 23.37 g, 39.17 g and 42.13 g for the treatments A, B, C, D and E, respectively, while the length increment for those treatments were 4.63 cm, 7.81 cm, 8.91 cm 1.5 cm and 11.05 cm, respectively. The water quality parameters were in the suitable range for fish growth.